Impact of Workload, Training, and Inspirations for Worker Performance at R-Hotel Rancamaya Bogor - Yanti, Yuli; Samsuri; Ismartaya (MultiTech Publisher, 2024)
The purpose of this study is to ascertain how employee performance at R-Hotel Rancamaya Bogor is impacted by workload, training, and motivation. Primary and secondary data make up the study's data 104 employees completed questionnaires that yielded primary data. On the other hand, secondary data came from pertinent company and other sources. This study used a survey approach along with a type of verification and descriptive research methodology. The questionnaire makes use of traditional assumption testing, reliability tests, and validity tests. Prior to doing multiple regression testing, the Likert scale is employed. This is done in order to ascertain how one dependent variable is affected by the four independent variables that were employed. Based on the findings of validity and reliability tests, which demonstrate that all indicators are deemed valid and reliable, the study's conclusions are drawn. Workload (X1), training (X2), and motivation (X3) all have an impact on employee performance (Y) at R-Hotel Rancamaya Bogor at the same time. Employee performance is impacted by all independent variables, however somewhat.